ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN RAWAT JALAN DI PUSKESMAS DUREN DAN PUSKESMAS BERGAS KABUPATEN SEMARANG TAHUN 2017 - Einurkhayatun, Biyanda; Suryoputro, Antono; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat (Undip), 2017)
Puskesmas (Community Health Clinic) as the Unit of Technical Implementation Health become the spearhead of health service. Puskesmas are required to improve the quality of performance in providing services. Outpatient is one of the services provided by Puskesmas. The number of outpatient visits in Puskesmas Semarang has decreased in the past two years. Puskesmas Duren and Puskesmas Bergas experienced as the highest decreased number of patient visits. There is still found some complaints such as long waiting times, the waiting room less comfortable,and less friendly officer. This study aims to determine the level of satisfaction and suitability between expectation and reality received by patients to outpatient services in Puskesmas Duren and Puskesmas Bergas of District Semarang based on the dimension aspects of service quality. This research use descriptive analytic method with cross sectional design. The sample of this research was 100 respondents. Data analysis used Importance Performance Analysis. The results of this study indicate the level of suitability between expectations and reality to the overall dimension of service quality is 79.70%. While the level of suitability of each dimension include tangible of 81.94%, reliability of 79.36%, responsiveness of 77.00%, assurance of 79.44%, and empathy of 80.88%. Suggestions for the puskesmas such as comfort the waiting room, adding supporting facilities, increasing the number of waiting chairs, adding information media, maximizing preventive promotive effort, be on time, the doctors deliver the results of examination and provide information about patient illness, polite and friendly in providing services, and effective communication.